Relationship between the features of information system (IS) quality and job satisfaction among non-academic staff at UiTM Melaka City Campus / Noorlidah Hj.Abu Bakar - Hj.Abu Bakar, Noorlidah (Faculty of Business Management, 2013)
This study was conducted to explain the relationship between the features of information system(IS) quality and job satisfaction among non-academic staff at UiTM Melaka City Campus. The study was carried out at UiTM Melaka City Campus. The study involved 120 respondents with non-academic staff from different department which include top level management, middle management and lower level management. the total sample size required is (N=92) based on table Krej-cie, Morgan and Daryle (l970). The main objective is to identify the level of job satisfaction among the non-academic staff at UiTM Me1aka City Campus. Moreover, researcher also investigate the relationship between the features of Information System Quality such as system quality, information quality, service quality and job satisfaction. The samples category are taken from the non-academic staff are collected by using the stratified random sampling from each category, with reference to the size of the category relative to the population. Furthermore, non-academic staff from different levels of employment may present different perceptive of the surveys. The result of the survey showed that the most fn~quently accepted the relationship between Information System(IS} Quality features and job satisfaction is high and moderate correlation.